2021
DOI: 10.3390/ijerph18126511
|View full text |Cite
|
Sign up to set email alerts
|

Impact of COVID-19 on Healthcare Workers in Brazil between August and November 2020: A Cross-Sectional Survey

Abstract: During the COVID-19 pandemic, healthcare workers (HCW) have been subjected to greater workloads. We conducted a cross-sectional online survey to assess the impact of the COVID-19 pandemic on Brazilian HCW. Data were collected between 11 August and 1 November 2020. Of the 295 respondents, 95 (32.2%) were medical doctors, 82 (27.8%) administrative staff, 53 (18.0%) nurses, 27 (9.2%) laboratory staff, and 38 (12.9%) were other staff. COVID-19-related restructuring at the health facilities was reported by 207 (70.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 53 publications
0
12
0
Order By: Relevance
“…Worldwide, the COVID-19 pandemic increased the rates of anxiety and depression among HCWs [ 51 ]. While HCWs play an important role in limiting the impact of COVID-19, their lives have been greatly affected by the pandemic [ 52 ].…”
Section: Discussionmentioning
confidence: 99%
“…Worldwide, the COVID-19 pandemic increased the rates of anxiety and depression among HCWs [ 51 ]. While HCWs play an important role in limiting the impact of COVID-19, their lives have been greatly affected by the pandemic [ 52 ].…”
Section: Discussionmentioning
confidence: 99%
“…For the validation of the content of the Diagnostic Label based on the proposed definition, the experts in the study completed a structured survey, which was divided into the following sections: [42][43][44][45], corresponding to: fear, helplessness, shortness of breath, psychomotor agitation, guilt, anger, stress, sadness, rage, irritability, panic attacks, disturbed sleep pattern, anxiety, dizziness, feeling of unreality, state of confusion, anguish, emotional exhaustion, depression, somatisation, flashbacks, depersonalisation (clinical and listless attitude towards other patients or people), feeling of dullness, hopelessness, intrusive thoughts, tiredness, social isolation, tension, tremors, weakness, gastrointestinal disorders (stomach pain, diarrhoea, nausea, etc. ), behavioural alterations (tobacco, alcohol, etc.).…”
Section: Instruments and Variablesmentioning
confidence: 99%
“…Risk factors for long COVID in non-hospitalized adults include female sex, socioeconomic deprivation, obesity, and a wide range of comorbidities [12]. Healthcare workers (HCWs) have been identified as a more vulnerable group to infection, due to their high frequency of occupational exposure [13, 14]. Recent studies have shown that most vaccinated individuals report improvement of long COVID symptoms [15].…”
Section: Introductionmentioning
confidence: 99%